Штучний інтелект – сучасний інструмент біомедичної інженерії - Скляров, Г. В. (ХНУРЕ, 2022)
The medicine of the future depends on the development of artificial intelligence, robotics and biotechnology. Artificial intelligence is used in many areas, and medicine is considered one of the most promising for using its capabilities. This work is devoted to on the ability to application of systems of artificial intelligence to the solving the problems of aging and longevity. On the basis of the possibilities of the most popular bioinformatics packages with an open code, there is an application of the best way for the completion of the tasks of biomedical engineering.